Inside Back Cover: Volume 3 Issue 4. Issue 4 (20th December 2022) - Sun, Fang‐Fang; Li, Wen‐Han; Huang, Zi‐Hang; Sun, Wenping; Dou, Yuhai; Yuan, Ding; Jia, Baohua; Ma, Tianyi
Abstract : Inside back cover image : In this work, the bottlenecks of low cost polypyrrole in term of practical application, such as insufficient electrochemical performances and poor cycling stability, have been solved by an optimized pulse‐potential polymerization strategy. This strategy effectively removed the concentration polarization effect during the electrodeposition process, leading to shorter molecular structure and homogeneous stress distribution of polypyrrole. In addition, the enhanced protonation level further boosted the charge transfer kinetics in polypyrrole. As a result, the optimized polypyrrole electrodes achieved outstanding specific capacitance and long cycle life simultaneously. The fabricated pouch supercapacitors of large size can exhibit a stable energy output and strong compressive endurance when suffering harsh scenarios of simulating real‐world, which provides a promising commercial prospect for polypyrrole‐based electrode materials. (DOI: https://doi.org/10.1002/smm2.1116 )